Selʹskij aktivist-učitelʹ - Šiškin, M. I. (KnigoGrad, 2010)
Writers of Mozhga region, saving of national tradtitions and pecularities of the folklore of village Pazyal.
Die Vorlage enth. insgesamt 2 Werke